Predictive validity and the impact of change in total LSI-R score on recidivism - Vose, Brenda (Criminal justice and behavior, 2013)
The Level of Service Inventory-Revised (LSI-R) is an assessment instrument designed to evaluate the risks and needs of offenders. The current study examines the predictive validity of the LSI-R with a sample of 2,849 probationers and parolees at two points in time. This design allows for the analysis of the instrument?s predictive validity at Time 1 and Time 2, and the correlation between changes in LSI-R scores and recidivism. The results suggest that the LSI-R is a valid assessment instrument for predicting recidivism and that change in LSI-R score is associated with change in risk of recidivism. The implications of these findings for effective correctional intervention are discussed.